Menghidupkan Ekosistem Penelitian: Strategi Promosi Layanan Pendukung Penelitian di Perpustakaan Universitas Sumatera Utara - Ade Yohana Lumbantoruan; Fransiska Timoria Samosir; Araf Aliwijaya (Journal of Education on Social Science (JESS), 2026)
The promotion of research support services at the University of North Sumatra (USU) Library has not been carried out evenly across all types of services, resulting in some services being less well known and not utilized optimally by library users. This study aims to analyze the promotion strategy for research support services at the University of North Sumatra (USU) Library based on the promotion mix framework. The research method used was descriptive qualitative through observation, document study, and interviews. Interviews were conducted with 11 informants who were selected purposively from among the leaders and service staff. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The research was mapped using the promotion mix framework. Research support services at the USU Library include subscriptions to international journal databases and various e-books, literature search ordering and assistance services, information literacy classes, article publication training, author profile development training, content similarity checking services (Turnitin), and institutional repositories. The promotion of research support services is carried out conventionally and digitally. The promotional tools used are banners, bulletin boards, socialization, websites, and social media (Instagram, Facebook, YouTube, TikTok). However, there are limitations in the form of uneven promotion between services and the fact that not all stages of the research support service cycle have been implemented. This study recommends improving the promotion strategy through personal selling and direct marketing.